The United States: The threat of a bad example: Undermining international standards as "war on terror"detentions continue - (:unkn) unknown (My University, 2016)
Report published by Amnesty International which states that the US administration’s actions since 11 September 2001 threaten to erode international law and standards forged over the past half-century or more.